Fibre cement boards as permanent formwork for reinforced concrete elements - Mowzer, Naashif (Department of Civil Engineering, 2024)
Formwork operations constitute the most expensive and time-consuming activity in the construction of concrete structures. A significant factor in the construction's time and cost components is the use of temporary formwork systems which have reusability limitations. Permanent formwork provides an alternative type of formwork that remains in place on the structure, and overcomes the reusability challenges of temporary formwork. Due to its permanent adherence to the structure and material composition, permanent formwork may have benefits that exceed time and cost savings. By bonding to the structure for the duration of its service life, it may improve underlying concrete's durability. The aim of this study was to assess if fibre cement boards, when used as a permanent formwork, can increase the durability of the underlying concrete and develop a sufficient bond to the concrete to act as a permanent formwork. The testing procedure resulted in the production of composite and reference concrete samples, two concrete mixes were produced to simulate good-quality and poor-quality concrete. Durability index, bulk diffusion, and modified interface shear bond tests were conducted. The modified shear bond test demonstrated that a bond with sufficient strength could be attained but further research is required to determine whether the bond is capable of withstanding differentials strains brought about by internal and external factors. Should proper controls not be in place, the bonding process may be susceptible to delamination. According to the durability index test results, the fibre cement boards did not improve nor decrease the concrete's durability. The results of the bulk diffusion tests showed that the composite samples had lower concentrations of chlorides indicating that the fibre cement boards provided protection to the underlying concrete. Additionally, the research showed that the fibre cement board functioned similarly good-quality concrete, indicating that under certain conditions, fibre cement concrete would be able to be specified as an equivalent concrete cover.